2020
DOI: 10.3390/microorganisms8071023
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Factors Shaping the Skin Microbiome

Abstract: Human skin, our most environmentally exposed organ, is colonized by a vast array of microorganisms constituting its microbiome. These bacterial communities are crucial for the fulfillment of human physiological functions such as immune system modulation and epidermal development and differentiation. The structure of the human skin microbiome is established during the early life stages, starting even before birth, and continues to be modulated throughout the entire life cycle, by multiple host-related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 102 publications
0
28
0
2
Order By: Relevance
“…Their lipid compounds promote the growth of lipophilic bacteria, such as Staphylococcus and Cutibacterium [ 63 ]. On the other hand, the increased level of skin hydration decreases sebum content and may reduce Cutibacterium number [ 95 ]. Lee et al [ 96 ] found that the application of a set of moisturizing products increased the bacterial diversity of the skin microbiome but reduced the number of Cutibacterium .…”
Section: Cosmetics and Clothing Textilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their lipid compounds promote the growth of lipophilic bacteria, such as Staphylococcus and Cutibacterium [ 63 ]. On the other hand, the increased level of skin hydration decreases sebum content and may reduce Cutibacterium number [ 95 ]. Lee et al [ 96 ] found that the application of a set of moisturizing products increased the bacterial diversity of the skin microbiome but reduced the number of Cutibacterium .…”
Section: Cosmetics and Clothing Textilesmentioning
confidence: 99%
“…Their antagonistic activity against pathogens may result from the competition, synthesis, and secretion of various antimicrobial substances or blocking their adhesion to skin cells [ 97 ]. One study showed that probiotic bacteria Lactobacillus rhamnosus , L. reuteri , L. acidophilus , L. delbrueckii and Bifidobacterium bifidum reduced the risk of developing AD and acne and were effective in wound healing when antibiotics failed [ 95 ]. Ointment containing L. reuteri DSM (German Collection of Microorganisms and Cell Cultures GmbH) 17938, a strain with proven antagonistic properties against skin pathogens, positively affected AD skin [ 97 ].…”
Section: Cosmetics and Clothing Textilesmentioning
confidence: 99%
“…Human skin plays an important role in protecting the body against infections by pathogens and harbors a diverse skin microbiota composed of bacteria, archaea, fungi, and viruses, of which bacteria are the most dominant [ 1 , 2 , 3 , 4 ]. Balanced colonization of the normal skin microbiota contributes to inhibiting adhesion of pathogens, whereas imbalanced colonization of an abnormal skin microbiota can lead to skin diseases/disorders [ 4 , 5 , 6 ]. Previous studies have reported microorganisms on the skin that are beneficial [ 7 , 8 ] or detrimental [ 9 , 10 ] to the physiological activity of cells [ 1 , 11 ], and a variety of physiological alterations triggered in the skin can be explained based on this information [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The skin microbiota is widely recognized to be of paramount importance for the maintenance of skin health. It is a dynamic ecosystem continuously exposed to intrinsic, host-related and extrinsic environmental factors which taken together contribute to its ecology [15]. Family and household contacts have been reported to have an important influence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also show that each individual has a unique personal microbial "cloud", emitting between 10 6 to 10 7 skin-associated microbes per h, resulting in a significant deposition of biomass in the built environment [17,18]. Other factors such as the ambient temperature and humidity, ventilation, co-occupancy, contact with the external environment, air quality and UV light are also contributing to the individual variation in skin microbiota colonization [15,19]. Even the amount of green areas and biodiversity in the vegetation surrounding the primary residence is an important factor shaping the composition of commensal microbiota and influencing immunotolerance [20,21].…”
Section: Introductionmentioning
confidence: 99%